2020
DOI: 10.1093/intqhc/mzaa170
|View full text |Cite
|
Sign up to set email alerts
|

Clinical handover and handoff in healthcare: a systematic review of systematic reviews

Abstract: Purpose The purpose of this systematic review is to appraise and summarize existing literature on clinical handover. Data sources We searched EMBASE, MEDLINE, Database of Abstracts of Reviews of Effects and Cochrane Database of Systematic Reviews. Study selection Included articles were reviewed independently by the review team. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 38 publications
0
32
0
6
Order By: Relevance
“…1 Ideally, the standardized handoff process is incorporated into the workflow of the electronic health record to guide the verbal exchange and eliminate wasting time by taking notes. 2 Standardized training on how to conduct a handoff from the role of a sender and a receiver has been identified as key to success. 1 Champions and coaches are suggested to serve as role models to promote the process.…”
Section: Preconditionsmentioning
confidence: 99%
See 3 more Smart Citations
“…1 Ideally, the standardized handoff process is incorporated into the workflow of the electronic health record to guide the verbal exchange and eliminate wasting time by taking notes. 2 Standardized training on how to conduct a handoff from the role of a sender and a receiver has been identified as key to success. 1 Champions and coaches are suggested to serve as role models to promote the process.…”
Section: Preconditionsmentioning
confidence: 99%
“…Desmedt et al2 conducted a review of systematic reviews and found some evidence that standardized and written handoffs resulted in improved teamwork, greater accuracy and consistency of information transfer, a decrease in the number of forgotten tasks, improved patient and provider satisfaction, and saved nursing time.They caution that good-quality research on handoff designs and their outcomes is limited and better-designed studies are required. A quality improvement approach is recommended to implement and sustain a highly reliable and high-quality handoff process 1…”
Section: Considering Nurses' Right To Work With a Reliable Processmentioning
confidence: 99%
See 2 more Smart Citations
“…Any concerns for postoperative complications, including the potential risk of haematoma, are highlighted during the sign out, and should be cascaded through explicit handovers which must take place when transferring to the PACU and thereafter the ward. This should include communication of postoperative risks and specific concerns of bleeding [ 78 , 79 ] (Grade C). Direct surgical handover of any concerns to PACU and/or ward nurses can enhance staff awareness and improve patient safety.…”
Section: Postoperative Communicationmentioning
confidence: 99%